Extending Uppsala model with springboard perspective in emerging multinational's sequential internationalisation: Evidence from a construction company's expansion in Africa - Ruosu Gao; Qiuling Gao; Xiaolin Zhuang; Kaiyang Sun (Journal of Risk and Financial Management, 2022)
The Uppsala model explains the traditional internationalisation process of multinational enterprises (MNEs), which gradually begin to internationalise from countries with smaller psychic distances. However, in the turbulent global economy, an increasing number of MNEs from emerging markets (EMNEs) adopts a more radical and aggressive approach, strategically using international expansion as a springboard to enter an overseas market and radiate surrounding countries and regions. By combining the springboard perspective and the Uppsala model, we analyse a series of processes from EMNE's first entry into an overseas market to the successful localisation and expansion of international business. This radical model of international expansion has not been thoroughly studied. This empirical study aims to address this research gap by using a qualitative method and an in-depth case study. This paper conducted a semi-structured interview with 16 expatriates, executives, and middle-level managers from the case company in 2016. As one of the few single case studies that systematically studies the internationalisation process of EMNEs and provides first-hand empirical evidence, it contributes to practice and provides a contextual reference for EMNEs.
Keywords: 330; Uppsala model; springboard perspective; emerging multinational enterprise; sequential internationalisation; environmental volatility